Pengaruh Perencanaan Anggaran, Pelaksanaan Anggaran, Kompetensi Sumber Daya Manusia dan Politik Anggaran Terhadap Penyerapan Anggaran di Kota Palembang - Febiola, Febi; Periansya; Fithri, Eka Jumarni (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The research aims to determine the effect of budget planning, budget implementation, human resource competence and budget politics on budget absorption in Palembang City. The research method used in this research is quantitative method. The data used is primary data in the form of questionnaires distributed to respondents. The population in this study were 32 OPDs of Palembang City with the sampling technique being saturated sampling. The questionnaires were distributed to 128 employees in 32 OPDs of Palembang City with 4 respondents each in each OPD. Based on the results of the study, it is known that Budget Planning, Budget Implementation and Budget Politics partially have a positive and significant effect on Budget Absorption, while Human Resource Competencies partially have no effect on Budget Absorption. Simultaneous tests show the results that the variables of Budget Planning, Budget Implementation, Human Resource Competencies, and Budget Politics together have an effect on Budget Absorption.